Cone-beam computed tomographic evaluation of dimensional hard tissue changes following alveolar ridge preservation with leucocyte and platelet-rich fibrin techniques: a pilot study - Passos da Silva, Natalia; Carlos Costa da Silva, Joao; Freitas, André; Margarida Cruzoé Rebello, Iêda; Yang, Ruijia; Wang, Tao; Zhao, Rusin; Nogueira, Getulio (Brazilian Dental Science, 2022)
Objective: This study evaluated the effect of leucocyte and platelet-rich fibrin (L-PRF) techniques used in alveolar ridge preservation on dimensional hard tissue changes of the alveolar ridge assessed using cone-beam computed tomography (CBCT) scans. Material and Methods: Elective alveolar ridge preservation surgeries were performed on seven systemically healthy patients who underwent single posterior tooth extraction. Patients were randomly treated with PRF mixed with a commercial bone xenograft (n = 3) or PRF plug (n = 4). CBCT scans were taken immediately after tooth extraction and then four months later, just before implant surgery. Dimensional alterations in socket height (SH), socket area (SA) and socket volume (SV) were evaluated on CBCT scans by percentage differences before and after treatments. Results: Sockets treated with PRF plus bone xenograft had a tendency to maintain alveolar bone dimensions over time (SH= 11.22% to 82.74%, SA= 1.84% to 48.91% and SV= 9.11% to 203.62%), while sockets treated only with PRF plug technique presented only a modest increase in height (SH= 1.47% to 11.11%) but greater alveolar ridge resorption confirmed by a decrease in socket area and volume dimensions (SA= 0.21% to -24.09% SV= 8.53% to -54.12%). Conclusion: Within the limitations of this study, the maintenance of alveolar socket dimensions was observed when PRF was associated with a xenograft. However, the loss of alveolar ridge dimensions was not entirely prevented by PRF treatment alone. KEYWORDS Alveolar bone loss; Bone substitutes; Cone-beam computed tomography; Platelet-rich fibrin; Tooth socket.